2009
DOI: 10.1021/ed800026d
|View full text |Cite
|
Sign up to set email alerts
|

You Can’t Get There from Here

Abstract: Large curricular changes of the 1960s brought about by the ChemStudy and Chemical Bond Approach initiatives were generally successful, but they also created learning problems. These were well recognized by a series of surveys in 1971. Recent surveys (2008) show that the same chemical difficulties for learners are still present in most “modern” curricula at all levels. This is despite the efforts of many international research projects designed to improve the learning of chemistry. The common factor in all thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
188
0
22

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(210 citation statements)
references
References 9 publications
0
188
0
22
Order By: Relevance
“…A dominant framework in chemistry education is the level-based description of representations (Johnstone 2010): the macro-level, the sub-micro level, and the symbolic level. Macrolevel phenomena and properties can be experienced with our senses, while the atomic processes underlying these directly observable phenomena occur at the sub-microscopic level, which must be represented using models, diagrams, or graphs.…”
Section: Temporal and Spatial Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…A dominant framework in chemistry education is the level-based description of representations (Johnstone 2010): the macro-level, the sub-micro level, and the symbolic level. Macrolevel phenomena and properties can be experienced with our senses, while the atomic processes underlying these directly observable phenomena occur at the sub-microscopic level, which must be represented using models, diagrams, or graphs.…”
Section: Temporal and Spatial Scalesmentioning
confidence: 99%
“…As already mentioned, three levels of organization (macro, sub-micro, and symbolic) have been recognized in level-based descriptions of representations (Johnstone 2010), but biology requires two additional (meso and micro) levels (Tsui and Treagust 2012;van Mil et al 2016), and natural selection encompasses the most extreme ranges of scales and complexity. Boroditsky (2000) proposed that abstract conceptual domains are structured through metaphorical mappings from domains grounded directly in experience.…”
Section: Temporal and Spatial Scales In Visualizationsmentioning
confidence: 99%
“…[1,2,35]). However, by developing competence in these skills, we believe that students will go a long way toward optimizing their ability to interpret and use ERs as effective knowledge-building and communication tools.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of a biological tissue, it might be necessary to translate between ERs that represent the visible and tangible macro-level, the microscopic level, as well as the molecular level of biological organization [35]. The ''distance'' of vertical translation required may not always involve a complete macro-micro-molecular transition but could also comprise smaller distances between levels of complexity [30].…”
Section: Translate Vertically Between Ers That Depict Different Levelmentioning
confidence: 99%
“…Indeed, one overriding feature of biology is the representation of knowledge at different systemic levels of organisation and scale. Recently, Johnstone (2010) has suggested that one of the main difficulties associated with learning science is that learners must 'move' between different representational levels that range from the 'macroscopic' to the 'symbolic'. Constructing knowledge at different representational levels is considered a crucial criterion for the successful learning of biology (Bahar, Johnstone and Hansell, 1999).…”
Section: Different Representational Levels Of Biological Conceptsmentioning
confidence: 99%